Penerapan Supervisi Klinis Teman Sejawat untuk Meningkatkan Kompetensi Pedagogik dan Kompetensi Profesioanal Guru SMAN I Pangkalan Kerinci - Risnita Risnita (MAJAMATH: Jurnal Matematika dan Pendidikan Matematika, 2021)
Clinical supervision can help teachers narrow the gap between ideal teaching and classroom application. The supervision is collaborative in order to improve teacher performance in the classroom. The purpose of this research is to increase the pedagogical and professional competence of teachers at High School 1 Pangkalan Kerinci, in the 2019-2020 school year in two cycles consisting of planning, implementing actions, observing and reflecting. The research data collected were pedagogical competence data, professional competence and field notes. The collected data were analyzed descriptively. The results of this research indicate that the application of peer clinical supervision can improve the pedagogical and professional competence of teachers at High School 1 Pangkalan Kerinci. Pedagogic competence from first cycle and second cycle has increased by 62.5%. Meanwhile, professional competence from first cycle and second cycle increased by 12.5%.